Value Orientation and its Relationship with Human Development Indexes (Economical and Social) in Bandarabbas City - mostafa zahirinia (توسعه اجتماعی)
Based on the Ronald Inglehart's theory of value transformation, the present paper intends to examine the condition of peoples' value orientation in order to investigate the relationship between social and economical indexes of human development and the type of value orientation. The data were obtained from 393 questionnaires completed by individuals aged between 18 and above in BandarAbbas through direct interview method. The analysis of the data revealed that 44.8% of respondents had material value orientation, 50% of them have both material and meta material value orientation while only 5.1 % of them have meta material value orientation. Thus, it may be concluded that people give higher priority to material values. Furthermore, the results show that younger individuals compared to older ones, and also individuals with higher education compared to those with lower education give more priority to meta material values. Therefore, considering the Scarcity hypothesis, which states that value priorities of a person is a reflection of his social and economical environment, it may be concluded that in the population investigated for this study, people prefer material values because their basic needs have not been fully satisfied. In addition, findings of the present study show that there is a meaningful relationship between variables such as education, parents' education, life expectancy, and the extent of the use of mass media and the type of value orientation that people have.